A Highly Sensitive and Signal-On Electrochemical Aptasensor Based on Restriction Endonuclease Induced Background Elimination. Issue 8 (16th May 2016) - Zhang, Songbai; Hu, Xia; Geng, Hongen; Huang, Meixin; Qiu, Yanqing; Shen, Congcong; Wang, Shuo; Shen, Guangyu; Yang, Minghui
Abstract : In this contribution, Sal I restriction endonuclease is used for the first time to develop a electrochemical aptasensing platform with eliminated background current for highly sensitive detection of cocaine. The sensing interface is easily fabricated by self-assembling only aptamer probe which is ingenious designed by integrating aptamer sequence for cocaine and recognition sequence for Sal I endonuclease. The recognition sites are reserved in the stem of the hairpin aptamer probe in the absence of cocaine and specifically cutoff with the treatment of endonuclease, resulting in removing of tagged ferrocene species away from the electrode surface and no peak current is observed. Binding with target cocaine induces structure-switching of designed aptamer probe and causes disappearance of cleavage sites for endonuclease. The integrated aptamer sequence is maintained on the electrode surface when exposing to Sal I endonuclease, generating a obvious peak current of ferrocene. By using this distinct electrochemical aptasensing strategy, cocaine can be sensitively detected with a low detection limit of 0.3 nM. Moreover, the proposed proof-of-principle of electrochemical aptasensing method exhibits unique characteristics of simple fabrication, easy control and universal application by skillfully designing the sequence of aptamer probe.